Pengaruh Hutang dan Persediaan Terhadap Laba Usaha PT. Indocement Tunggal Prakarsa Tbk - Baiq Adzatin Maghfiroh dan Yolanda (Fakultas Ekonomi Universitas Borobudur, 2016)
This study aims to determine the effect of the Debt and Inventory Operating Income either partially or simultaneously at PT. Indocement Tbk. Total population in the study is a quantitative method. Total population in this financial statements and the study sample research, counted as many as 8 to 32 year period. The sampling technique using purposive sampling. The variable in this study is the independent variable (independent) consisting of Debt, Inventory and the dependent variable (dependent) is Operating Profit. The results showed that the debt effecting significant partially on Operating Profit. The stocks are effected significant partially on Operating Profit. Simultaneously, debt and stocks creating a significant effect on Operating Profit level determination coefficient to 61%